Regulation of soleus muscle properties by mechanical stress and/or neural activity - Fuminori Kawano; Naoya Nakai; Yoshinobu Ohira (Japanese Society of Physical Fitness and Sports Medicine, 2012)
The responses of soleus muscle and/or muscle fibers to gravitation loading and/or unloading and the roles of mechanical stress and/or neural activity in the regulation of morphological properties in the soleus muscle were briefly reviewed. The soleus muscle, one of the ankle plantar flexors, shows tonic activity during body weight support against gravity (weight bearing exercise?). Passive shortening of muscle length and inhibition of the electromyogram (EMG) activity level are noted if rats are exposed to microgravity or hindlimb-unloading by tail suspension, which lead to severe atrophy in soleus muscle fibers. Previous studies reported that the unloading-related inhibition of mechanical stress and/or neural activity caused down-regulation of muscle mass. On the contrary, functional overload by amputation of the peripheral tendons or ablation of the synergists (plantaris and gastrocnemius) increased force production and sensory nerve activity in the soleus muscle, resulting in fiber hypertrophy. However, deafferentation at the L4-5 segmental level of the spinal cord down-regulated muscle mass, although the loss of muscle mass was not induced if the functional overload was performed in addition to deafferentation. These observations indicate that both mechanical stress and neural activity play important roles in the regulation of soleus muscle mass. It is well known that the level of protein synthesis and degradation strongly affects muscle mass. The mechanical stress-induced recruitment of satellite cells is also one of the important pathways in up- or down-regulation of fiber size. The essential roles of mechanical load applied to muscle fibers and neural activity of the muscle itself were clearly suggested by the reports cited in the present review.